ALTERNATIF PENINGKATAN PARTISIPASI IBU RUMAHTANGGA MASYARAKAT LOKAL DALAM PERLINDUNGAN MATA AIR DI KAWASAN HUTAN RINJANI LOMBOK TENGAH - L. Sukardi; Halimatus Sa’diyah; Syarif Husni (JURNAL AGRIMANSION, 2015)
ABSTRACT The aim of this study were to: (1) analyze the determinants of housewife participation in spring water protection movement (well-known as PERMATA, Perlindunganmata air); (2) assess the alternatives for increasing awareness and participation of housewives in the movement; and (3) design a model of and strategies for spring protection and conservation in ways that are participatory and sustainable the forest area of Rinjani in Central Lombok.The research was conducted in Forest Area of Rinjani in Central Lombok, i.e. in the districtsof BatukliangUtara and Kopang. The collection of data and information is done through the approach/technique of in-depth interviews, focus group discussions (FGD) and direct observation. The results showed that the determining factors in the lack of participation of housewives in the movement are: (1) lack of socialization the PERMATA program, (2) lack of economic incentives, (3) no regulations governing the involvement of housewives, and (4) no involvement of housewives in conservation planning. Alternativesfor increasing participation can be done through: (1) awareness improvement (2) provision of the exemplary and directions from role models, and (3) campaigns and publications of PERMATA movement. The most likely model of and strategies for spring protection and conservation in participatory and sustainable way is the housewife economic empowerment, among others through the development of family forest, small business development in NTFPs, and the development of compensation conservation.